Associations of the Weekend Warrior Physical Activity Pattern with Mild Dementia: Findings from the Mexico City Prospective Study - De Moraes-Ferrari, G (BMJ Publishing Group, 2025)
Objectives To investigate associations of the weekend warrior physical activity pattern with mild dementia. Methods Participants in the Mexico City Prospective Study were surveyed from 1998 to 2004 and re-surveyed from 2015 to 2019. Participants were asked about leisure time physical activity at baseline. Those who exercised up to once or twice per week were termed weekend warriors and those who exercised more often were termed regularly active . A Mini Mental State Examination (MMSE) was used to assess mild dementia at re-survey. Cox models were adjusted for age, sex, education, income, blood pressure, smoking, body mass index, civil status, sleep, diet and alcohol at baseline. The attributable fraction was defined as the proportion of cases that would not exist if all adults were to exercise once or twice per week or more often. Results The analysis included 10 033 adults of mean (SD) age 51 (10) years followed for 16 (2) years. There were 2400 cases when mild dementia was defined as a score of ≤22 on the MMSE. Compared with the group that reported no sport or exercise, the hazard ratio was 0.75 (95% CI 0.61 to 0.91) in the weekend warrior group, 0.89 (95% CI 0.78 to 1.02) in the regularly active group and 0.84 (95% CI 0.75 to 0.95) in the combined group. The attributable fraction was 13% (95% CI 5% to 21%). Similar results were observed when mild dementia was defined as a score of ≤23 on the MMSE. Conclusions This longitudinal analysis suggests that the weekend warrior physical activity pattern is associated with a reduced risk of mild dementia. © Author(s) (or their employer(s)) 2025.